Factors Influencing the Digital Transformation of Universities in Thailand - Laorach, Chanchira; Tuamsuk, Kulthida (International Journal of Innovative Research and Scientific Studies, 2022)
Rapid advances in digital technology have brought about changes in the administration and operations of all kinds of organizations. Those that are able to efficiently transform themselves into digital organizations in a short time and have a high capacity for self-adjustment to the new socio-economic situation achieve competitive advantages. Many universities in Thailand have committed to a strategy of transformation into digital organizations. This research was conducted to study the factors behind the success of the digital transformation of Thai universities, using a quantitative research method. The data were collected using a questionnaire administered to 495 administrators from 6 Thai universities, of whom 303 were high-level administrators, 174 middle-level administrators, and 18 low-level administrators. Statistical analyses and confirmatory factor analysis were performed on the data obtained. The results revealed 6 factors that influence the success of digital transformation in the context of Thai universities: 1) digital culture, 2) digital strategies, 3) management process, 4) organization leaders, 5) digital technologies, and 6) staff. The results are useful for academics and organizations’ administrators or authorities to set clearer directions to propel their operations towards digital success.